Evaluation of the expression of the immunosuppressive enzyme – indoleamine 2,3-dioxygenase in ovarian cancer tissue - Rogala, Ewelina; Nowicka, Aldona; Bednarek, Wiesława; Barczyński, Bartłomiej; Piekarczyk, Wanda; Klimek, Katarzyna; Zakrzewski, Maciej; Kotarski, Jan (Menopause Review/Przegląd Menopauzalny, 2013)
Introduction : Tumor progression is associated with the function of the immune system. Recent studies have shown that indoleamine 2,3-dioxygenase (IDO) is one of the molecules involved in tumor-induced immunosuppression. IDO probably induces tumor progression through inhibiting NK cells and T lymphocytes activity. Aim of the study : The aim of our study was to assess indoleamine 2,3-dioxygenase at the mRNA level in ovarian serous and endometrial adenocarcinoma. Material and methods : Forty patients (15 before and 25 after menopause) operated due to advanced ovarian carcinoma were recruited. mRNA expression of IDO was assessed by means of real-time PCR. The control group was represented by normal ovary tissue. Results : Indoleamine 2,3-dioxygenase was expressed at the mRNA level in all ovarian cancer patients. It was significantly higher (p < 0.005) in cancer tissue than in healthy controls (RQ = 0.040). The expression of IDO in serous ovarian cancer (RQ = 0.319) was significantly higher (p = 0.02) compared with the expression in endometrioid cancer (RQ = 0.091). The expression of IDO in ovarian cancer patients with clinical stage III was higher than in patients with clinical stage II, but this difference did not reach statistical significance. There was no statistically important difference between the expression of IDO in ovarian cancer patients in relation to grading and menopausal status. Conclusions : IDO positive expression is different among the histological types.